2013
DOI: 10.3109/13693786.2013.824123
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis jiroveciihaplotypes at the internal transcribed spacers of the rRNA operon in French HIV-negative patients with diverse clinical presentations ofPneumocystisinfections

Abstract: Pneumocystis jirovecii, a transmissible fungus, is the causative agent of pulmonary infections. Its genomic diversity has appeared in reports from around the world but data on P. jirovecii genotypes in France are still limited. This study describes the typing of P. jirovecii isolates from 81 HIV-negative patients monitored at Brest University Hospital, Brittany, France, 40 of whom developed Pneumocystis pneumonia (PcP), and remaining 41 patients were colonized by the fungus. The isolates were assayed at the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
3
1
Order By: Relevance
“…In our study, one previously undescribed subtype was found, ITS type Bj. None of the ITS typed samples suggested mixed infection, in contrast to a large percentage of mixed infections found in other studies (Matsumura et al , 2011; Le Gal et al , 2013; Rabodonirina et al , 2013; Sheikholeslami et al , 2013).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, one previously undescribed subtype was found, ITS type Bj. None of the ITS typed samples suggested mixed infection, in contrast to a large percentage of mixed infections found in other studies (Matsumura et al , 2011; Le Gal et al , 2013; Rabodonirina et al , 2013; Sheikholeslami et al , 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…However, in a recent study conducted in Iran, no difference was shown in the most prevalent subtype in patients either infected with HIV, or with an underlying malignancy or with an acute exacerbation of chronic obstructive pulmonary disease (Sheikholeslami et al , 2013). A recent French study (Le Gal et al , 2013) showed a high percentage of Ec and Ai (8.9 % each) in HIV-negative patients either colonized with P. jiroveci or suffering from PCP. In our study, both HIV-positive and HIV-negative patients were included.…”
Section: Discussionmentioning
confidence: 98%
“…So far, the epidemiological studies on P. jirovecii ITS genotypes in Europe, Africa, America and other Asian countries showed that there have been at least 62 ITS genotypes reported in GenBank [1]. Genotype 1 was the most common ITS genotypes based on worldwide studies [18][19][20][21][22][23]. The most prevalent genotype of ITS in Japan was Genotype 10 [24], which was observed in our study.…”
Section: Discussionsupporting
confidence: 67%
“…Thus, the presence of genotype 2 in the aforementioned CF infant may reflect particular geographical characteristics of the fungus in infants living in this region. ITS haplotype Jf has rarely been described in France, whatever the patient population (range, 0–7.5%), whereas Eg is the most frequent haplotype (range, 42.8–64.5%) (Nevez, 2003 ; Le Gal et al, 2013b , 2015b ). The presence of type Jf in this infant could simply be a random event.…”
Section: Discussionmentioning
confidence: 99%